The effect of providing students with behavioral goals on their academic achievement in the ninth grade physics course - Olayan, Juma Adeeb (Journal of Educational and Psychological Sciences, 2021)
This study examined the effect of pre-knowledge behavioral objectives in ninth grade student’s achievement and retention of social education material. This study tried to answer the question: is there a significant effect for the pre-knowledge behavioral objectives in ninth grade student’s achievement and retention of social education material? The sample of the study was (54) students of ninth grade, were divided into two groups, experimental and control. The experimental group was informed of the behavioral objectives, but the control group was not informed of these objectives, the same method was followed in teaching both groups. In this study, the researcher has used behavioral objectives, and achievement test consisting of 26 items covered the list of behavioral objectives prepared by researcher himself for the purpose of study. The T-test analysis of variance was used to test the influence of teaching strategy on achievement and retention of social education material. The result of the first post-test has shown that there are no significant differences at (α = 0.05) in the ninth grade students achievement. the result of the second post-test has shown that there are no significant differences at (α = 0.05) in the in ninth grade in retention of social education material. According to the result of this study, recommendation is given in conclusion of this study, showing they no importance of using behavioral objectives as strategy of teaching in the learning process.